ROLE DES TRANSPORTS DANS LE RAVITAILLEMENT D’ASSINIE EN BIENS DE CONSOMMATION (LITTORAL SUD-EST IVOIRIEN) - Seydou, Ouattara; Joseph, Kablan N’guessan Hassy (European Scientific Journal, ESJ, 2015)
The purpose of this article is to show the contribution of transports in the availability of food products to Assinie. The collection of secondary data gave an important place in documentary research in the documentation and information centers and administrations. Our analysis also anchored in the direct observation of facts. In addition, we have undertaken open interviews with resource persons. The result of these methodological tools shows that the development of tourism is realized at the expense of agricultural activities which nevertheless allow ensuring the population's feed. Hence, their supply of consumer goods depends on the surrounding communities and more distant. The efficiency of transports appears as a vital necessity due mainly to poverty of the soil for food crops. But also, beyond food concerns, the configuration of the site due to the river system that imposes spatial discontinuities, equips transports role of territorial integrators. They are suddenly an interesting importance for relational life of Assinie, its inhabitants and the development of trade.